Preliminary Outcome of a Novel Edge-to-Edge Closure Device to Manage Mitral Regurgitation in Dogs - Liu, Bo; Leach, Stacey B.; Pan, Wenzhi; Zheng, Fangyu; Jia, Liujun; Zhou, Xueying; Li, Jing (Frontiers in Veterinary Science, 2020)
Background: Veterinary management of mitral valve regurgitation due to mxyomatous valve disease in dogs is limited to medical treatments, which only postpones the onset of congestive heart failure or alleviates clinical symptoms. Most surgical procedures to manage this condition in humans require cardiopulmonary bypass and have a high risk of complications. Animals: Eight dogs with naturally occurring mitral valve regurgitation. Methods: Prospective observational study. All dogs were treated with a novel edge-to-edge transcatheter device named ValveClamp. The total surgical procedural time and total catheterization time were recorded. Echocardiographic variables measured pre- and post-procedure were compared using Wilcoxin-signed rank test with a P-value < 0.05 considered significant. Data were expressed as median and interquartile range and absolute numbers and percentages. Results: The procedural success rate was 100% and all the dogs survived without complications. The mean total surgical procedural time was 86.1+12.3 minutes and the mean catheterization time was 27.6+7.5 minutes. Echocardiography revealed a significant reduction in mitral regurgitation severity in all dogs following the procedure based on both a reduced mitral regurgitant maximum jet area (P = 0.012) and a reduced mitral regurgitant maximum jet area to left atrial area (P = 0.018). Conclusion: The ValveClamp device is effective at reducing the severity of mitral regurgitation in dogs with naturally occurring myxomatous valve disease.